Vogt-Koyanagi-Harada in a Kadazan female - Andrew Keat Eu Lim, FRCS, M.Med; Shueh Lin Lim, MRCP; Elias Hussein, MS (Philippine Journal of Ophthalmology)
Objective: To report a case of Vogt-Koyanagi-Harada in a Kadazan girl, a member of an indigenous race of the state of Sabah, Malaysia.